Evaluation of the stability and ecotoxicological profile of nanostructured lipidic systems containing ginger essential oil compared to its free form - Pinto, Cláudia Grigolo; Fruet, Gabriela Guarenti; Rech, Virginia Cielo; Vasconcellos, Noeli Júlia Schüssler de; Fernandes, Liana da Silva (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
The ginger essential oil presents medicinal properties of interest, but it has a low solubility and a high toxicity, which limits its use in the health area. Through the production of nanostructured systems, these damages can be minimized without reducing their medicinal properties. The bioassays conducted on ecotoxicity with Artemias salina, the free ginger essential oil, and nanostructured systems of the lipidic carrier type aimed to check if these systems can protect the active, in order to improve its bioavailability and to reduce its toxicity. The evaluation of ecotoxicity with Artemias salina showed a significant reduction in the toxicity of the nanostructured systems when compared to the positive control and the oil in its free form. Given the results obtained in this study, we can conclude that the nanostructured systems tested do not present ecotoxicity and therefore have great potential for use in nanomedicine, thus contributing to the use of products of plant origin in nanotechnology when applied to health care.